Greening the Production of Indigo Blue Exploiting Light and a Recombinant Synechocystis sp. PCC6803 Strain Expressing the Enzyme mFMO - Giovanni Loprete; David Rubert; Francesco Bellusci; Nikola Lončar; Marco W. Fraaije; Elisabetta Bergantino (Microbial Biotechnology)
ABSTRACT Cyanobacteria are emerging as interesting cell factories, offering the significant advantage of their in‐built photosynthetic machinery, which generates NADPH to support redox biocatalysis. In this study, we assessed the potential of the cyanobacterium Synechocystis sp. PCC6803 in producing the dye indigo by light‐driven whole‐cell biotransformation using indole as a starting compound. A stable transgenic strain expressing a flavin‐containing monooxygenase from Methylophaga aminisulfidivorans (mFMO) was engineered, enabling light‐dependent indigo production. Upon optimising conditions, effective biotransformations could be performed, resulting in 112 mg/L indigo (86% conversion of the furnished indole). Additionally, we present a method for the recovery of the secreted dye directly from the growth medium through solid‐phase absorption on polyamide nets. Overall, the effectiveness and sustainability of the biotransformation in Synechocystis sp. PCC6803 performed at the laboratory scale provide a strong basis for further exploring the applicability of the process.